PRAME and CTCFL-reactive TCRs for the treatment of ovarian cancer - van Amerongen, Rosa A.; Tuit, Sander; Wouters, Anne K.; van de Meent, Marian; Siekman, Sterre L.; Meeuwsen, Miranda H.; Wachsmann, Tassilo L. A.; Remst, Dennis F. G.; Hagedoorn, Renate S.; van der Steen, Dirk M.; de Ru, Arnoud H.; Verdegaal, Els M. E.; et al. (Frontiers in Immunology, 2023)
Recurrent disease emerges in the majority of patients with ovarian cancer (OVCA). Adoptive T-cell therapies with T-cell receptors (TCRs) targeting tumor-associated antigens (TAAs) are considered promising solutions for less-immunogenic ‘cold’ ovarian tumors. In order to treat a broader patient population, more TCRs targeting peptides derived from different TAAs binding in various HLA class I molecules are essential. By performing a differential gene expression analysis using mRNA-seq datasets, PRAME, CTCFL and CLDN6 were selected as strictly tumor-specific TAAs, with high expression in ovarian cancer and at least 20-fold lower expression in all healthy tissues of risk. In primary OVCA patient samples and cell lines we confirmed expression and identified naturally expressed TAA-derived peptides in the HLA class I ligandome. Subsequently, high-avidity T-cell clones recognizing these peptides were isolated from the allo-HLA T-cell repertoire of healthy individuals. Three PRAME TCRs and one CTCFL TCR of the most promising T-cell clones were sequenced, and transferred to CD8+ T cells. The PRAME TCR-T cells demonstrated potent and specific antitumor reactivity in vitro and in vivo. The CTCFL TCR-T cells efficiently recognized primary patient-derived OVCA cells, and OVCA cell lines treated with demethylating agent 5-aza-2′-deoxycytidine (DAC). The identified PRAME and CTCFL TCRs are promising candidates for the treatment of patients with ovarian cancer, and are an essential addition to the currently used HLA-A*02:01 restricted PRAME TCRs. Our selection of differentially expressed genes, naturally expressed TAA peptides and potent TCRs can improve and broaden the use of T-cell therapies for patients with ovarian cancer or other PRAME or CTCFL expressing cancers.